2020
DOI: 10.1001/jamanetworkopen.2020.16278
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Neurofilament Light Levels With Long-term Brain Atrophy in Patients With a First Multiple Sclerosis Episode

Abstract: IMPORTANCE Data are needed on the potential long-term prognostic association of serum neurofilament light in multiple sclerosis (MS). OBJECTIVE To evaluate serum neurofilament light as a biomarker associated with long-term disease outcomes in clinically isolated syndrome. DESIGN, SETTING, AND PARTICIPANTS This post hoc cohort study used data from the Controlled High-Risk Avonex Multiple Sclerosis Prevention Study, a 36-month, multicenter, placebocontrolled interferon β-1a randomized clinical trial conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The increased axonal damage assessed by sNfL in IRL patients complements the knowledge of the destructiveness of IRLs ( 17 ) in terms of their association with higher lesion burden, atrophy, prominent black holes, and the worse clinical and neuropsychological outcome described earlier ( 8 , 9 ). Our findings, therefore, are consistent with chronic inflammation and increased sNfL ( 44 ) and with the reported associations between increased sNfL, increased lesion burden, and atrophy ( 14 , 42 ). Furthermore, neurofilament is assigned a value as a predictor of long-term clinical outcome ( 12 ) and is thought to be weakly associated with neuropsychological impairment ( 48 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increased axonal damage assessed by sNfL in IRL patients complements the knowledge of the destructiveness of IRLs ( 17 ) in terms of their association with higher lesion burden, atrophy, prominent black holes, and the worse clinical and neuropsychological outcome described earlier ( 8 , 9 ). Our findings, therefore, are consistent with chronic inflammation and increased sNfL ( 44 ) and with the reported associations between increased sNfL, increased lesion burden, and atrophy ( 14 , 42 ). Furthermore, neurofilament is assigned a value as a predictor of long-term clinical outcome ( 12 ) and is thought to be weakly associated with neuropsychological impairment ( 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…sNfL is reported to have a prognostic value for the conversion from clinically isolated syndrome to clinical-definite MS ( 46 ). Furthermore, sNfL levels assessed early from disease onset are reported to correlate significantly with 10-year follow-up MRI parameters, such as T2 lesion load and whole-brain atrophy and fatigue ( 14 , 37 , 47 ) and with long-term clinical motor outcome after 15 years ( 12 ) but only weakly with the long-term evolution of cognitive performance ( 48 ). Nevertheless, sNfL research is currently in its early stages, and a normative database of sNfL in healthy individuals is still needed including the effects of age and comorbidities ( 41 , 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the volume reduction of the gray matter, bilateral putamen, caudate nucleus, and nucleus accumbens was correlated with the increase in plasma NfL concentration. Previous studies have shown that the decrease in brain volume is the result of a variety of pathological mechanisms, including irreversible demyelination, axonal and neuronal damage [19]. Recent studies have shown that a reduction in the cortical, and deep nucleus volumes, mainly in the putamen, caudate, and globus pallidus, was correlated to the increased Global Assessment Scale (GAS), Bold: results significant (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of reagents stored at their recommended storage conditions of 2-8°C was assessed by monitoring the measured drift of QC samples. QCs were tested on Day 0, 3,7,10,14,17,21,24,28,31,72,123. Linear regression analysis of concentration versus time for each sample was performed.…”
Section: Reagent Storage Stabilitymentioning
confidence: 99%